Modernist women and visual cultures : Virginia Woolf, Vanessa Bell, photography, and cinema - Humm, Maggie, 1945- (Edinburgh University Press, 2002)
This volume takes some of the visual aspects of modernism - photo albums and image-texts - and examines the ways in which modernist women explore a freer range of aesthetics in their work.